The perspectives of clients and unqualified allopathic practitioners on the management of delivery care in urban slums, Dhaka, Bangladesh - a mixed method study - Wahed Tasnuva; Moran Allisyn C; Iqbal Mohammad (BMC, 2010)
Abstract Background BRAC is implementing a program to improve maternal and newborn health among the urban poor in the slums of Bangladesh (Mansohi), funded by the Bill & Melinda Gates Foundation. Formative research has demonstrated that unqualified allopathic practitioners (UAPs) are commonly assisting home-delivery. The objective of this study was to explore the role of unqualified allopathic practitioners during home delivery in urban slums of Dhaka. Methods This cross-sectional study was conducted between September 2008 and June 2009 in Kamrangirchar slum in Dhaka, Bangladesh, using both qualitative and quantitative research methods. Through a door-to-door household survey, quantitative data were collected from 463 women with a home birth and/or trial of labor at home. We also conducted seven in-depth interviews with the UAPs to explore their practices. Results About one-third (32%) of the 463 women interviewed sought delivery care from a UAP. We did not find an association between socio-demographic characteristics and care-seeking from a UAP, except for education of women. Compared to women with three or more pregnancies, the highest odds ratio was found in the primi-gravidity group [odds ratio (OR): 3.46; 95% confidence interval (CI): 1.65-7.25)], followed by women with two pregnancies (OR: 2.54; 95% CI: 1.36-4.77) to use a UAP. Of women who reported at least one delivery-related complication, 45.2% received care from the UAPs. Of 149 cases where the UAP was involved with delivery care, 133 (89.3%) received medicine to start or increase labor with only 6% (9 of 149) referred by a UAP to any health facility. The qualitative findings showed that UAPs provided a variety of medicines to manage excessive bleeding immediately after childbirth. Conclusion There is demand among slum women for delivery-related care from UAPs during home births in Bangladesh. Some UAPs' practices are contrary to current World Health Organization recommendations and could be harmful. Programs need to develop interventions to address these practices to improve perinatal care outcomes.